2002
DOI: 10.1080/07391102.2002.10506808
|View full text |Cite
|
Sign up to set email alerts
|

The HMG1 Ta(i)le

Abstract: We have studied structural changes in DNA/protein complexes using the CD spectroscopy, upon the interaction of HMG1-domains with calf thymus DNA at different ionic strengths. HMG1 protein isolated from calf thymus and recombinant HMG1-(A+B) protein were used. Recombinant protein HMG1-(A+B) represents a rat HMG1 lacking C-terminal acidic tail. At low ionic strength (15 mM NaCl) we observed similar behavior of both proteins upon interaction with DNA. Despite this, at higher ionic strength (150 mM NaCl) their int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…The HMGB1 protein showed cooperativity in HMGB1-DNA binding. It was previously shown that increase in the concentration of HMGB1 in the system facilitates DNA binding and results in the formation of ordered supramolecular complexes (Polianichko et al, 2002(Polianichko et al, , 2013. The formation of these supramolecular complexes also explains the observed difference in complex mobility with increase in protein concentrations.…”
Section: Discussionmentioning
confidence: 59%
“…The HMGB1 protein showed cooperativity in HMGB1-DNA binding. It was previously shown that increase in the concentration of HMGB1 in the system facilitates DNA binding and results in the formation of ordered supramolecular complexes (Polianichko et al, 2002(Polianichko et al, , 2013. The formation of these supramolecular complexes also explains the observed difference in complex mobility with increase in protein concentrations.…”
Section: Discussionmentioning
confidence: 59%
“…The spectral behavior of the complexes in the UV region is different for the Mn 2þ -DNA-protein complex than for the DNA-protein 36,43,68,69 and Mn 2þ -DNA 52 complexes and depends on the protein to DNA ratio. The ECD spectra of the complexes indicate that several structural stages are occurring in the system, depending on the protein to DNA ratio (Figure 3), and supramolecular structures are formed during these stages.…”
Section: Discussionmentioning
confidence: 96%
“…18,23,[26][27][28][29][30][31][32][33] Protein-protein interactions affect many DNA binding properties of HMGB1, especially in complex DNA-protein systems. [34][35][36] It was shown recently that HMGB proteins modulate some recombination events. [13][14][15][16] Histone H1 is one of the most studied chromatin proteins.…”
Section: Introductionmentioning
confidence: 99%
“…10,13,18,[20][21][22] Protein-protein interactions affect strongly DNA-binding properties of HMGB1 especially in complex DNA-protein systems. [23][24][25] Histone H1 is one of the best studied chromatin proteins. [26][27][28][29] It binds to linker DNA at the entrance or exit of the nucleosome.…”
Section: Introductionmentioning
confidence: 99%